Kajian Eksistensi Distribusi Hukum Pangkat Pada Kota-Kota di Indonesia - Zawani, Hoferdy; Pradono, Pradono (Journal of Regional and City Planning, 2007)
The  notion  of  Power-law  which arguably  stands  for  the  sign of  complex  system  has  been  widely  encountered  in  many  natural  and  social phenomenons  as  upon which  we  hypothesize  Indonesian  cities’  size distribution  would  follow  the  same  manner.  To  evaluate  it,  we  test  the hypothesis  employing  hybrid  method  co-joined  the  Cumulative Distribution  Function  (CDF)  technique,  Hill  Estimator,  and  Anderson Darling  Statistics  (Coronel-Brizio,  dkk,  2003;  Coronel-Brizio  and Hernandez-Montoya, 2004) on Indonesian cities’ population at year 1990 and  2005.  As  results,  in  one  hand,  our  work  brings  quantitative  sight upon Indonesian cities distribution within which were satisfied by  Powerlaw  distribution  for  both  year  1990  (Xmin=9665  and Alpha=2,088±0,094)  and  year  2005  (Xmin=129490  and Alpha=1,994±0,078)  while  in  the  other  hand, it  strengthens  the  precede Power-law  Indonesian  cities  distribution  claim  which  previously proposed  by  Mulianta, dkk (2004).  Put the  result altogether  and  have it tested with deductive and simulation method as we try to explain on how the distribution could ever happen have lead us to conceive the notion of ‘onslaught’  urbanization  in Indonesia. All and all,  the work solidifies the edge  of  chaos  paradigm  in  Indonesian  urban  and  regional  planning study.